2020
DOI: 10.1155/2020/5291714
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Effectors Play Essential Roles in Acute Respiratory Infection Caused by Klebsiella pneumoniae

Abstract: Innate immune effectors constitute the first line of host defense against pathogens. However, the roles of these effectors are not clearly defined during Klebsiella pneumoniae (K. pneumoniae) respiratory infection. In the current study, we established an acute pneumonia model of K. pneumoniae respiratory infection in mice and confirmed that the injury was most severe 48 h post infection. Flow cytometric assay demonstrated that alveolar macrophages were the predominant cells in BALF before infection, and neutro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
7
13
0
Order By: Relevance
“…Clinical strains of A. baumannii SJZ24, SJZ26, and SJZ09 were isolated from Bethune International Peace Hospital in Shijiazhuang, China, in 2016 ( Zeng et al, 2019 ). P. aeruginosa strain XN-1 ( Gao et al, 2020 ), K. pneumoniae strain YBQ ( Liu et al, 2020 ), and S. pneumoniae were isolated from Chongqing Southwest Hospital. S. aureus strain KM-22 was isolated from the Second Affiliated Hospital of Kunming Medical University ( Zeng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Clinical strains of A. baumannii SJZ24, SJZ26, and SJZ09 were isolated from Bethune International Peace Hospital in Shijiazhuang, China, in 2016 ( Zeng et al, 2019 ). P. aeruginosa strain XN-1 ( Gao et al, 2020 ), K. pneumoniae strain YBQ ( Liu et al, 2020 ), and S. pneumoniae were isolated from Chongqing Southwest Hospital. S. aureus strain KM-22 was isolated from the Second Affiliated Hospital of Kunming Medical University ( Zeng et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The recruitment of neutrophils to the lungs during infection is essential for bacterial clearance and to avoid its dissemination. Indeed, depletion of neutrophils increases the bacterial burden in the lungs of mice infected with K. pneumoniae [ 7 , 8 ]. At the site of infection, activated neutrophils play a fundamental role in bacterial killing by a range of antimicrobial tools [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the work showed that CCR2 + monocytes were the main producers of TNF-α in infected mice. Work carried out in mice challenged with clinical isolates of K. pneumoniae also showed increases in the pulmonary levels of TNF-α, IL-1β, IL-6 [32], CXCL1, MCP-1, and MIP-2 [33], as well as neutrophil infiltration in the respiratory tract [32,33].…”
Section: Discussionmentioning
confidence: 93%
“…On the other hand, studies carried out in immunocompetent mice infected with the clinical isolates K. pneumoniae KPC+ or OXA-48+ showed that doses of 10 7 CFUs or higher are necessary to achieve a respiratory infection that reaches densities of 6-7 log 10 CFUs/g lung [31]. Similarly, doses of 10 8 CFUs were required to achieve respiratory infections in adult C57BL/6 [32] and BALB/c [33] mice with clinical isolates of K. pneumoniae. Consistent with these studies, doses of 10 7 CFUs or higher of LABACER 01 or LABACER 27 were required in this study to achieve respiratory infection in adult immunocompetent BALB/c mice.…”
Section: Discussionmentioning
confidence: 99%